Comparative Study on the Carcass Traits of Commercial Native Chicken, Backyard Native Chicken, Commercial Broiler and Spent Layer Chicken - Sathishkumar, R.; Kulkarni, V. V.; Chandirasekaran, V.; Vasan, P.; Muthulakshmi , M. (Journal of Meat Science, 2019)
To study the effect of class of chicken on the carcass traits an experiment was conducted on 12 birds of either sex in each commercial  native chicken, backyard native chicken, commercial broiler and spent layer chicken. Birds were slaughtered by Jatka method and carcass  traits were recorded. Live weight, dressed carcass weight, dressing percentage and meat: bone ratio was significantly higher (P
Keywords: Carcass traits; Meat bone ratio; Indigenous and broiler poultry